(untitled) (Fiep Bulletin - online, 2016)
The present study aimed to investigate the manifestations of violence among students in Community Sports project and intervene pedagogically through a round of conversation in the construction of human values ??and the minimization of the main manifestations of violence in the Mondubim neighbourhood in Fortaleza. The specific objectives were to identify and classify the manifestations of violence occurring in the project classes according to type: symbolic, verbal and physical; check if there are variations of violence between age groups; and also build together new rules and better matched to pupils living in the project. Participant observation and a table to record constructed by the authors, containing a list of the main aggressive attitudes and behaviours that might occur during the execution of the class: a descriptive study, the quantitative type using the following instruments was performed. The sample consisted of 40 male students, 15 with a mean age equivalent to 10.3, and 25 students with approximately 15 years. The fieldwork took place in two weeks, a total of five classes for each class. At the end of the survey it was found that major violence occurred were symbolic and verbal and students of age group 7-12 years behaved more aggressively than the age of 12 years onwards. Therefore, the rules and agreements are a possible way to minimize outbreaks of violence occurred in social projects.